Immune dynamics throughout life in relation to sex hormones and perspectives gained from gender-affirming hormone therapy - Ahmet Yalcinkaya; Ahmet Yalcinkaya; Rumeysa Yalcinkaya; Fabian Sardh; Fabian Sardh; Nils Landegren; Nils Landegren (Frontiers in Immunology)
Biological sex is closely associated with the properties and extent of the immune response, with males and females showing different susceptibilities to diseases and variations in immunity. Androgens, predominantly in males, generally suppress immune responses, while estrogens, more abundant in females, tend to enhance immunity. It is also established that sex hormones at least partially explain sex biases in different diseases, particularly autoimmune diseases in females. These differences are influenced by hormonal, genetic, and environmental factors, and vary throughout life stages. The advent of gender-affirming hormone therapy offers a novel opportunity to study the immunological effects of sex hormones. Despite the limited studies on this topic, available research has revealed that testosterone therapy in transgender men may suppress certain immune functions, such as type I interferon responses, while increasing inflammation markers like TNF-α. Transgender women on estrogen therapy also experience alterations in coagulation-related and inflammatory characteristics. Furthermore, other possible alterations in immune regulation can be inferred from the assessment of inflammatory and autoimmune markers in transgender individuals receiving hormone therapy. Understanding the complex interactions between sex hormones and the immune system, particularly through the unique perspective offered by gender-affirming hormone therapies, may facilitate the development of targeted therapies for infections and autoimmune diseases while also improving healthcare outcomes for transgender individuals. Here we review immune dynamics throughout life in both sexes and provide a summary of novel findings drawn from studies exploring gender-affirming hormone therapy.